2022
DOI: 10.1002/app.53113
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylidene fluoride/polysulfone/air plasma defected hexagonal boron nitride emerging nano blends for electrostatic dissipation

Abstract: In the present era electrostatic dissipation (ESD) property is crucial for packaged electronic device to protect from humidity over long duration. It was important to control the ESD for better integrated packaged electronic gadgets. Polymer blends and composites were modified with nano fillers as a promising area for ESD applications. In the present investigation, polyvinylidene fluoride (PVDF)/polysulfone (PSF) was modified by untreated (UT) and air plasma treated (PT) hexagonal boron nitride (h‐BN) by solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 116 publications
2
2
0
Order By: Relevance
“…The presence of uniformly dispersed fillers within the polymer host system indicates a substantial interaction between the polymer and filler networks. This interaction confirms that fillers are incorporated into host polymer, potentially enhancing the surface properties of polymer matrix [48]. In the case of the PVB/ PEDOT:PSS blend, strong interfacial adhesion without defects or voids is observed.…”
Section: Scanning Electron Microscopy Of Ppm Electrodesupporting
confidence: 53%
See 1 more Smart Citation
“…The presence of uniformly dispersed fillers within the polymer host system indicates a substantial interaction between the polymer and filler networks. This interaction confirms that fillers are incorporated into host polymer, potentially enhancing the surface properties of polymer matrix [48]. In the case of the PVB/ PEDOT:PSS blend, strong interfacial adhesion without defects or voids is observed.…”
Section: Scanning Electron Microscopy Of Ppm Electrodesupporting
confidence: 53%
“…Upon modification with MoS 2 , a slight reduction in surface area and average surface roughness is noted. This could potentially be attributed to the occupation of micro voids by MoS 2 [48]. However, it is observed that this Mo-S (44) modification yields a synergistic impact on surface topography, resulting in a strong coupling between polymer filler system.…”
Section: Afm Analysis Of Ppm Electrodementioning
confidence: 99%
“…65 We adapted same method utilized in our previous study, whole process and setup of lee's disk method was explained in the same literature study. 43,66 Figure 14a respectively, as shown inset curve of Figure 14a which is in mutual agreement with reported literature. 67 The variation of K of PAN/NC showed increased trend with NC loading.…”
Section: Thermal Conductivity Of Pan/nc Polymer Blendssupporting
confidence: 92%
“…It may occupied micro surface pores leading to a soft surface. 36,48 It is further confirmed by scanning electron microscopy (SEM) shown in Figure 2a,b. Moreover, the roughness of pure EVA decreased when CNTs and MoS 2 were added.…”
Section: Morphological Analysis Of Polymer Nanocompositesmentioning
confidence: 62%